A high corrosion-resistant zinc-aluminum-magnesium alloy plated sheet and a continuous hot plating process

CN122727701APending Publication Date: 2026-09-11SHANDONG LANTIAN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611134241.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-09-11

AI Technical Summary

Technical Problem

[0004]为了解决因相关的锌铝镁镀层中κ-MgZn2相在镀后凝固与长期服役过程中易发生粗化长大而导致镀层耐蚀性能随服役时间逐步衰减的问题,本申请提供一种高耐蚀锌铝镁合金镀层板材及连续热镀工艺

Benefits of technology

[0033] 1. This application utilizes Al and Mg falling into the ternary eutectic high corrosion-resistant window, and introduces trace amounts of B and Sn; B, due to its low solubility, agglomerates in the κ phase and hinders coarsening at the eutectic grain boundaries, while Sn safely enters the plating bath after Al and Mg have blocked the Fe-Zn channels, and dissolves at the cut to form Sn-containing nano-barriers that impede Cl⁻ migration; pre-oxidation and incomplete reduction leave FeO on the steel substrate surface. x Nano islands, when placed in the pot, generate Fe-BO type interface nails in situ as κ phase nuclei anchor points, which promote their non-random arrangement and make the Fe-Al inhibition layer embedded in the steel base in a serrated shape; thus, the plate can achieve simultaneous improvement in three aspects: cut corrosion resistance, planar corrosion resistance and bending adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122727701A_ABST
    Figure CN122727701A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of metal corrosion prevention, and particularly discloses a high-corrosion-resistance zinc-aluminum-magnesium alloy plated plate and a continuous hot plating process. The zinc-aluminum-magnesium alloy plated layer comprises the following components in percentage by mass: Al: 1.8-2.5 wt%, Mg: 1.0-2.0 wt%, B: 0.001-0.005 wt%, Sn: 0.03-0.08 wt%, and the rest is Zn. The preparation method comprises the following steps: S1, pre-oxidation treatment: performing controlled pre-oxidation treatment on a cold-rolled steel plate after reduction annealing to obtain an oxidized base plate; S2, incomplete reduction treatment; S3, plating solution preparation and melting; S4, hot dipping and plating layer adhesion; and S5, low-temperature temperature control and cooling winding. The plate can be used for outdoor high-humidity environment components such as buildings, automobiles and household appliances, and has the advantages of simultaneously improving notch corrosion resistance, plane corrosion resistance and bending adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of metal corrosion protection technology, and more specifically, it relates to a high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet and a continuous hot-dip galvanizing process. Background Technology

[0002] Hot-dip galvanized aluminum-magnesium alloy coated steel sheets are a new generation of high-performance protective materials in the field of metal corrosion protection. Based on traditional hot-dip galvanizing and zinc-aluminum alloy coatings, a ternary synergistic protection system is constructed by introducing magnesium. It has been widely used in outdoor high-humidity and high-salt-spray service scenarios such as building envelope components, automotive body parts, home appliance casings, and photovoltaic brackets. This type of coating combines the sacrificial anode cathodic protection of zinc, the dense oxide film barrier effect of aluminum, and the self-healing properties of magnesium corrosion products. Its planar salt spray resistance can reach several to more than ten times that of traditional pure zinc coatings. It also has a certain self-healing protection capability for areas damaged by cuts, scratches, etc. At the same time, it is suitable for continuous hot-dip galvanizing industrial production and has good stamping formability and coating compatibility. It is gradually replacing traditional galvanized and aluminum-zinc coated materials and has become the mainstream development direction in the field of high-end corrosion-resistant steel sheets.

[0003] In terms of cut protection, conventional zinc-aluminum-magnesium (ZAM) coating technologies rely on the migration and deposition of Mg and Zn ions into the damaged area during corrosion. Under high chloride ion conditions, they are insufficient in inhibiting the initial corrosion of the exposed steel substrate at the cut, leading to early red rust formation. The stability and long-term effectiveness of cut protection under thin coating systems are still significantly lacking. In terms of planar corrosion resistance, the κ-MgZn2 phase in the coating is prone to coarsening and growth during post-coating solidification and long-term service. Grain boundary element segregation forms preferential corrosion channels, causing the coating's corrosion resistance to gradually decline over service time. In terms of bending adhesion, the Fe-Al inhibition layer between the steel substrate and the coating often exhibits a vertical columnar crystal growth pattern, with the interface bonding mainly consisting of mechanical interlocking. Repeated bending deformation easily leads to crack initiation along the interface and causes coating peeling. Summary of the Invention

[0004] To address the problem that the corrosion resistance of zinc-aluminum-magnesium alloy coatings gradually decreases over time due to the coarsening and growth of the κ-MgZn2 phase during post-plating solidification and long-term service, this application provides a high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet and a continuous hot-dip galvanizing process.

[0005] In a first aspect, this application provides a high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet, employing the following technical solution:

[0006] A high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet includes a steel substrate and a zinc-aluminum-magnesium alloy coating formed on the surface of the steel substrate. The zinc-aluminum-magnesium alloy coating contains the following components by mass percentage: Al: 1.8–2.5 wt%, Mg: 1.0–2.0 wt%, B: 0.001–0.005 wt%, Sn: 0.03–0.08 wt%, with the balance being Zn. The zinc-aluminum-magnesium alloy coating contains a κ-MgZn2 phase, which is in a spherical state and is non-randomly arranged with Fe-BO type interface nails distributed in the interface region between the steel substrate and the coating as nucleation anchors. An Fe-Al inhibition layer is provided between the steel substrate and the coating, and the Fe-Al inhibition layer is embedded in the steel substrate in an undulating serrated shape on the side facing the steel substrate.

[0007] By adopting the above technical solutions, the mass percentages of Al and Mg in the coating fall within the high corrosion resistance window of the zinc-aluminum-magnesium ternary eutectic system, enabling the formation of a dense zinc-based chloride hydroxylate and layered bimetallic hydroxide self-repairing film during planar corrosion. B has extremely low solubility in the zinc matrix; after entering the plating bath, it agglomerates in a forced agglomeration manner at the grain boundary region between the κ-MgZn2 phase and the ternary eutectic, hindering the coarsening of the κ phase during high-temperature plating and subsequent service. The introduction of Sn breaks the technical prejudice against using Sn in pure zinc coatings. Given that Al and Mg in the zinc-aluminum-magnesium system have already formed an Fe-Al inhibition layer blocking the Fe-Zn channel, Sn will not induce liquid metal embrittlement. Furthermore, in the early stages of corrosion at cuts or scratches, Sn selectively dissolves and forms a Sn-containing nano-oxidation barrier on the steel substrate surface, inhibiting the migration of chloride ions to the steel substrate. On the substrate side, FeO is pre-retained on the steel substrate surface through pre-oxidation and incomplete reduction. x Nano islands, FeO when placed in zinc pot x Fe-BO type interface nails are generated in situ at the three-phase interface by the reaction of B and molten Zn-Al-Mg in the plating solution. These nails also serve as nucleation anchors for the κ-MgZn2 phase, causing the κ phase to be arranged non-randomly with the nails as sites. The Sn segregation channels that match these nails also show a corresponding distribution. The Fe-Al inhibition layer changes the traditional vertical growth mode of columnar crystals due to the presence of the nano Fe-O transition layer, and instead becomes a serrated embedded steel substrate, improving the strain coordination ability between the inhibition layer and the steel substrate. The synergy of the above-mentioned plating solution components, interface structure and nucleation mode simultaneously improves the plate in terms of cut corrosion resistance, planar corrosion resistance in chloride ion environment and bending adhesion.

[0008] Preferably, the zinc-aluminum-magnesium alloy coating further includes one or more auxiliary modifying components selected from Re, Ti, or Sr, and the total content of the auxiliary modifying components is 0.01 to 0.3 wt% based on the total mass of the coating being 100 wt%.

[0009] By employing the above technical solution, Re element purifies trace oxygen and inclusions in the plating bath and modifies the grain boundary composition of the Fe-Al inhibition layer. Ti, in the form of hard microparticles or intermediate alloy inclusions, disperses at the κ phase boundary or η-Zn grain boundary, playing a pinning and refining role. Sr tends to modify the solidification mode of the η-Zn matrix and make FeAl3-Zn x The columnar densification, with all three components superimposed on the main B and Sn system, does not interfere with the formation of Fe-BO nails and the non-random arrangement of the κ phase, providing further room for grain refinement and interface modification beyond the main formulation.

[0010] Preferably, when the auxiliary modifying component contains Re, the Re is Ce or La; when the auxiliary modifying component contains Ti, Ti exists in the form of Al-Ti master alloy inclusions or TiB2 / TiC ceramic particles at the κ-MgZn2 phase boundary or η-Zn matrix grain boundary of the coating, and its total Ti content is 0.01-0.15 wt%; when the auxiliary modifying component contains Sr, Sr is introduced in the form of trace Sr-Zn master alloy, and its total Sr content is 0.005-0.05 wt%.

[0011] By adopting the above technical solutions, the combination of light rare earth elements such as Ce or La for Re can balance the cost of impurity removal and the effect of grain boundary modification in zinc-aluminum-magnesium melt, avoiding the excessive cost brought by heavy rare earth elements. If Ti is added as pure titanium powder or coarse Ti particles, it is easy to agglomerate in the plating solution and form local Ti-rich inclusions. Therefore, it can be introduced in the form of Al-Ti master alloy during the Al melting stage to pre-disperse Ti in the matrix, or it can be added in the form of pre-made TiB2 / TiC ceramic particles in the middle and late stages of plating solution mixing and suspended by airflow agitation, so that it eventually resides at the κ phase boundary or η-Zn grain boundary. Sr has high activity in zinc liquid. Introducing it in the form of Sr-Zn master alloy can reduce burn-off and make it uniformly dispersed in η-Zn matrix. Its lower limit ensures the modification effect, and the upper limit avoids excessive agglomeration, which leads to an increase in the amount of slag on the coating surface.

[0012] Preferably, the spheroidization rate of the κ-MgZn2 phase is ≥85%, and the equivalent circle diameter distribution of the κ-MgZn2 phase along the cross-sectional direction is 80-250 nm.

[0013] By adopting the above technical solution, after the κ phase completes the curing-driven spheroidization through low-temperature relaxation after plating, the distribution range of spheroidization rate and equivalent circle diameter matches the locking density of Fe-BO interface nails. If the spheroidization size is too small, the total surface area of ​​the κ phase will be too large and the Sn segregation channels will be too fragmented. If the spheroidization size is too large, the spacing between the κ phases in the eutectic network will be too wide and the barrier coverage after Sn dissolution will decrease. When the equivalent circle diameter falls within the above range, the κ phase completes spheroidization under the constraint of Fe-BO nails without net migration. The spatial correspondence between the spheroidized κ array and the Sn channels is maintained. During the bending process, the strain transfer between the η-Zn matrix and the κ phase is more continuous, and the tendency of the coating to crack and peel off is reduced.

[0014] Secondly, this application provides a continuous hot-dip galvanizing process for high corrosion-resistant zinc-aluminum-magnesium alloy coated sheets, employing the following technical solution:

[0015] A continuous hot-dip galvanizing process for a high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet includes the following steps:

[0016] S1. Pre-oxidation treatment: Controlled pre-oxidation treatment is performed on cold-rolled steel sheets after reduction annealing to obtain an oxide substrate.

[0017] S2. Incomplete reduction treatment: The oxide substrate is subjected to incomplete reduction treatment in a hydrogen-containing reducing atmosphere to obtain a pretreated substrate.

[0018] S3. Plating solution preparation and melting: Take Al, Mg, Sn and a portion of Zn for batching. Melt Al and a portion of Zn first, then add Mg and Sn raw materials to mix and obtain a basic melt. Then introduce B into the basic melt in the form of Al-B intermediate alloy or boron powder and mix evenly. Add the remaining Zn to adjust the bath height to obtain a zinc-aluminum-magnesium alloy plating solution.

[0019] S4. Hot-dip plating and coating adhesion: The pretreated substrate is immersed in the zinc-aluminum-magnesium alloy plating solution to complete the hot-dip reaction and then taken out. The amount of wet coating on one side of the strip is controlled to be 60-300g / m², and a substrate with wet coating is obtained.

[0020] S5. Low-temperature temperature control and cooling winding: The substrate with the wet coating is placed under airflow to allow the coating to solidify and the κ-MgZn2 phase to spheroidize in situ. Then, it is cooled and wound up to obtain a high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet.

[0021] By adopting the above technical solution, S1 introduces controlled pre-oxidation in reverse after reduction annealing, transforming the substrate surface, which is typically clean-faced during continuous line annealing, into a substrate carrying a nanocrystalline Fe-O transition layer, thus reserving FeO for the incomplete reduction of S2. x The oxide substrate of the nano-island; S2 partially reduces the Fe-O layer rather than completely reduces it by controlling hydrogen concentration, temperature, and residence time, retaining the FeO.x Nano-islands have a non-stoichiometric structure, and the proportion of O atoms is adjusted by hydrogen concentration and residence time. Pre-reduction purging removes loose portions from the oxide layer surface to prevent these loose materials from detaching and entering the plating bath during loading, forming inclusions or adhering to the substrate surface and causing plating defects. S3 addresses the characteristic that boron (B) is almost insoluble in zinc bath and has an extremely high melting point by introducing B using an Al-B master alloy as a carrier, or by suspending it with boron powder, ensuring that the final B concentration in the plating bath falls within the target range and does not form localized agglomerates. The Al in the Al-B master alloy also participates in the main components of the plating bath without introducing additional impurities. Auxiliary modifying components are added at staggered times according to their affinity for Al or Zn to avoid burn-off or agglomeration. In S4, the pretreated substrate is loaded into the bath at the moment of loading, and FeO... x Nano-islands, molten Zn-Al-Mg-Sn-B, and steel substrate undergo an interfacial reaction at the three-phase interface to generate Fe-BO type interfacial nails in situ. This reaction occurs simultaneously with the growth of the Fe-Al inhibition layer in the hot-dip galvanizing process, causing the inhibition layer to transform into a serrated embedded morphology. Sn enters the coating with the plating solution and enters the κ phase and eutectic interface in a segregated state. The single-sided adhesion amount is controlled to ensure that the coating thickness falls within the usable range of conventional products on a continuous line. In step S5, a low-temperature static setting is performed during the warm window between plating and quenching, allowing the κ phase to complete spheroidization under the locking effect of the Fe-BO nails without net migration. Subsequently, the product is obtained by cooling and coiling. In the above five steps, S1 and S2 are the interfacial prerequisites for the interaction between B and Sn on the plating solution side, and S3 is the dissolution of B into the plating solution and its reaction with FeO. x The reaction requires the following preconditions: S4 is the three-stage synergistic reaction initiation stage, and S5 is the finishing stage for κ spheroidization and array maintenance. The absence of any step will lead to a decrease in the synergistic effect of the subsequent steps.

[0022] Preferably, in step S1, the controlled pre-oxidation treatment is as follows: after the reduction annealing, the steel plate is introduced into a temporary storage section containing an oxygen atmosphere, and the temperature is controlled at 550-620°C and the residence time is 3-8s, so that a nanocrystalline Fe-O transition layer with a thickness of 20-50nm is oxidized and grown on the surface of the steel plate; wherein the oxygen atmosphere is air or a mixture of air and nitrogen, and the oxygen volume fraction is 0.5-5.0%.

[0023] By adopting the above technical solution, the substrate surface after reduction annealing directly enters the nitrogen-hydrogen reduction section for cleaning in a conventional continuous line. This application, however, reverses this process by using an oxygen-containing atmosphere to conduct short-term oxidation in a temporary storage section between annealing and pot entry. The oxidation temperature and residence time are coordinated to control the Fe-O layer thickness at the nanoscale, avoiding incomplete reduction due to excessive oxidation, which could lead to incomplete plating or poor adhesion. It also avoids insufficient oxidation causing FeO to become coated. xThe subsequent formation density of the islands is too low; the oxygen volume fraction is achieved by diluting the air to slow down the oxidation rate and facilitate the uniform nucleation of the nanocrystalline Fe-O layer. This nanocrystalline layer serves as the initial state for incomplete reduction in the subsequent S2, and its thickness and crystallinity directly determine the FeO content. x The final size and areal density of the nanoislands indirectly determine the pin density of the Fe-BO type interface pins and the scale of the non-random arrangement of the κ phase in S4.

[0024] Preferably, in step S2, the volume fraction of H2 in the hydrogen-containing reducing atmosphere is 5-15 vol%, with the balance being N2, the reduction treatment temperature is 480-560°C, and the residence time is 2-6 s; before the incomplete reduction treatment, the process further includes: dust removal or purging treatment of the oxide substrate surface to remove loose oxide particles.

[0025] By employing the above technical solution, the hydrogen concentration and temperature are combined to induce partial reduction rather than complete reduction of the nanocrystalline Fe-O layer, thus preserving the FeO. x Nano-islands are non-stoichiometric structures, and their O atom ratio is adjusted by hydrogen concentration and residence time. Pre-reduction purging removes loose portions from the oxide layer surface to prevent these loose materials from detaching and entering the plating bath during loading, forming inclusions, or adhering to the substrate surface and causing plating defects. The pretreated substrate surface at S2 outlet is characterized by: a steel substrate surface layer consisting of reduced Fe grains with discretely distributed FeO. x The nano-islands and the spaces between them form a clean Fe surface. When this state enters S4, it simultaneously satisfies the normal growth of the Fe-Al inhibition layer and the FeO... x The in-situ generation of Fe-BO nails at the islands, and the clean Fe region between the islands ensure that the bond between the inhibition layer and the steel base is not deteriorated due to pre-oxidation.

[0026] Preferably, in step S3, the mass fraction of B in the Al-B master alloy is 0.5–4 wt%; the introduction is as follows: after the basic melt temperature reaches 440–465°C, the Al-B master alloy is added in small batches with stirring, so that the final concentration of B in the plating solution falls within the range of 0.001–0.005 wt%; one or more auxiliary modifying components selected from Re, Ti, or Sr can also be selectively added. When Ti is added, it is added in the form of Al-Ti master alloy during the Al melting stage. When Re is added, it is added in the form of mixed rare earth Zn-Re master alloy before the remaining Zn is added.

[0027] By adopting the above technical solution, the melting point of boron (B) is much higher than the operating temperature of zinc-aluminum-magnesium plating solution, and its equilibrium solubility in zinc solution is extremely low. If pure boron powder is added directly, it is prone to floating and clumping, or the formation of boride agglomerates due to excessively high local concentrations. Therefore, an Al-B master alloy containing B is used as a carrier. The compatibility of Al with the plating solution matrix allows B to be dispersed in the melt in the form of atoms or nanoclusters after melting in the Al-B fragments. The base melt temperature falls within the upper-middle limit of the plating solution's operating window to ensure sufficient melting and removal of the Al-B master alloy without localized overcooling of the plating solution. Adding small pieces in batches and continuous stirring avoids single-point peaks in B concentration. Ti has an affinity for Al in the auxiliary modification components, so it is added in the form of Al-Ti master alloy during the Al melting stage. This allows Ti to be pre-dispersed in the Al phase before the subsequent addition of Mg and Sn, avoiding the formation of coarse Ti-Mg intermetallic compounds in the Mg-containing melt. Re has high activity, so it is added in the form of Zn-Re master alloy before Zn replenishment. This allows Zn liquid to support Re and reduces the oxidation loss of Re at high temperatures. The timing of Sr introduction should be coordinated with the Zn melting stage. It is added in the form of Sr-Zn master alloy during Zn replenishment to avoid Sr segregation in the melt with high Mg content.

[0028] Preferably, in step S4, the temperature of the hot-dip plating solution is 450–460°C, and the immersion time is 2–6 seconds. Before immersing the pretreated substrate in the zinc-aluminum-magnesium alloy plating solution, the pretreated substrate is further subjected to surface pretreatment: the surface of the pretreated substrate is coated with an alcoholic solution or aqueous solution containing boron compounds as a boron source pre-adsorption layer, wherein the boron compounds are boric acid, borate, or organic borate esters, and the coating amount is 0.05–0.5 mg / m² converted to elemental boron. After coating, the substrate is dried with hot air at 60–120°C for 5–20 seconds.

[0029] By adopting the above technical solution, the plating bath temperature is matched with the dissolution window of Al and Mg in zinc bath and the formation window of ternary eutectic. The immersion time and belt speed are matched to ensure that the Fe-Al inhibition layer thickness falls within the conventional range of continuous line products. Before entering the bath, the pre-treated substrate is coated with a B source pre-adsorption layer to make the FeO on the substrate surface... x The local B concentration at the nano-islands is higher than the B concentration in the bulk plating solution at the moment of entry into the bath, thus enhancing the FeO plating process. x The driving force of the three-phase interface reaction between B and molten Zn-Al-Mg further increases the pin density of the Fe-BO interface compared to methods relying solely on B in the plating bath. The alcohol or aqueous solution, acting as a carrier, volatilizes during the hot air drying stage without leaving carbon residue. The combination of drying temperature and time ensures that the boron-containing compounds remain in the FeO layer before the substrate is placed in the plating bath. x The surface does not absorb moisture and fall off; after entering the pot, B in the plating solution and B pre-adsorbed on the surface jointly supply the generation of Fe-BO nails, and Sn enters the coating at the same time and enters the κ phase and eutectic interface in a segregated state. The amount of single-sided adhesion is controlled so that the coating thickness is suitable for subsequent processing applications.

[0030] Preferably, in step S5, the resting is maintained at a temperature of 160-185°C for 30-50 seconds; then, the surface temperature is cooled by airflow to 80-120°C before water quenching or direct air cooling to room temperature to complete the winding.

[0031] By adopting the above technical solution, the substrate with wet coating has a temperature range in the continuous air-cooling section from the time it leaves the pot until it is quenched. This application transforms this range into a process window for κ phase spheroidization instead of simple rapid cooling. 160-185℃ is in the effective kinetic range of κ-MgZn2 phase ripening-driven spheroidization in the zinc-aluminum-magnesium ternary eutectic and is much lower than the melting point of zinc, so it will not cause coating softening or abnormal zinc spangle. Since the κ phase is already non-randomly arranged in S4 with Fe-BO nails as anchor points, the κ phase is locked by the nails during the spheroidization process and does not undergo net migration. After spheroidization, the spatial correspondence between the κ array and the Sn segregation channel is maintained, and the strain coordination is improved during bending. The substrate is first cooled to 80-120℃ by airflow and then quenched in water to avoid thermal shock wrinkles caused by direct water immersion at around 185℃. This is obvious for thin specifications. For thick specifications, direct air cooling to room temperature is used instead. After winding, a plate with coating structure and interface structure that meet the requirements is obtained.

[0032] In summary, this application has the following beneficial effects:

[0033] 1. This application utilizes Al and Mg falling into the ternary eutectic high corrosion-resistant window, and introduces trace amounts of B and Sn; B, due to its low solubility, agglomerates in the κ phase and hinders coarsening at the eutectic grain boundaries, while Sn safely enters the plating bath after Al and Mg have blocked the Fe-Zn channels, and dissolves at the cut to form Sn-containing nano-barriers that impede Cl⁻ migration; pre-oxidation and incomplete reduction leave FeO on the steel substrate surface. x Nano islands, when placed in the pot, generate Fe-BO type interface nails in situ as κ phase nuclei anchor points, which promote their non-random arrangement and make the Fe-Al inhibition layer embedded in the steel base in a serrated shape; thus, the plate can achieve simultaneous improvement in three aspects: cut corrosion resistance, planar corrosion resistance and bending adhesion.

[0034] 2. In this application, Re, Ti, or Sr are preferably used as auxiliary modifying components; Ti serves as an Al-Ti master alloy or ceramic microparticles residing at the κ phase boundary or η-Zn grain boundary to provide pinning; Re purifies the plating solution and modifies the Fe-Al inhibition layer grain boundaries; and Sr densifies FeAl3-Zn. x Columnar crystals; all three are compatible with the B and Sn main system and can be superimposed. Without disrupting the formation of iron boron oxygen nails and the non-random arrangement of the κ phase, the microstructure is further refined and the interface is modified, thereby achieving the effect of improving coating quality and corrosion resistance stability.

[0035] 3. In this application, it is preferable to coat the substrate surface with a boron-containing compound solution as a pre-adsorption layer for the B source before it is placed in the pan; this layer enhances the adsorption capacity of FeO.x The localized B concentration at the nanoislands enhances the driving force of the three-phase interface reaction, further improving the density and uniformity of Fe-BO nails; combined with the matching of the pre-oxidation atmosphere and incomplete reduction parameters, FeO was achieved. x The island size, nail density, κ phase arrangement scale and Sn channel coverage are simultaneously controlled to achieve the effect of maintaining consistent barrier coverage and bending adhesion stability at the cut cross-section. Attached Figure Description

[0036] Figure 1 This is a flowchart of a continuous hot-dip galvanizing process for a high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet proposed in this application.

[0037] Figure 2 This is a schematic diagram showing the detection results of the first appearance time of red rust in the embodiments and comparative examples of this application;

[0038] Figure 3 This is a schematic diagram showing the detection results of the percentage of red rust area in the 720h smoke test of the embodiments and comparative examples in this application;

[0039] Figure 4 This is a schematic diagram showing the detection results of the 0.01Hz low-frequency impedance modulus in the embodiments and comparative examples of this application;

[0040] Figure 5 This is a schematic diagram showing the test results of the number of times the coating peeled off during repeated 180° bending in the embodiments and comparative examples of this application. Detailed Implementation

[0041] The present application will be further described in detail below with reference to the accompanying drawings and embodiments.

[0042] Technical concept:

[0043] This application discloses a high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet and a continuous hot-dip galvanizing process. It includes a steel substrate and a zinc-aluminum-magnesium alloy coating formed on the surface of the steel substrate. The zinc-aluminum-magnesium alloy coating comprises the following components by mass percentage: Al: 1.8–2.5 wt%, Mg: 1.0–2.0 wt%, B: 0.001–0.005 wt%, Sn: 0.03–0.08 wt%, with the balance being Zn. The preparation method is as follows: S1, pre-oxidation treatment: a controlled pre-oxidation treatment is performed on a cold-rolled steel sheet after reduction annealing to obtain an oxide substrate; S2, incomplete reduction treatment; S3, plating solution preparation and melting; S4, hot-dip galvanizing and coating adhesion; S5, low-temperature temperature control and cooling winding.

[0044] This application utilizes Al and Mg falling into the ternary eutectic high corrosion-resistant window, and introduces trace amounts of B and Sn; B, due to its low solubility, agglomerates in the κ phase and hinders coarsening at the eutectic grain boundaries, while Sn safely enters the plating bath after Al and Mg have blocked the Fe-Zn channels, and dissolves at the cut to form a Sn-containing nano-barrier that impedes Cl⁻ migration; pre-oxidation and incomplete reduction leave FeO on the steel substrate surface. x Nano islands, when placed in the pot, generate Fe-BO type interface nails in situ as κ phase nuclei anchor points, which promote their non-random arrangement and make the Fe-Al inhibition layer embedded in the steel base in a serrated shape; thus, the plate can achieve simultaneous improvement in three aspects: cut corrosion resistance, planar corrosion resistance and bending adhesion.

[0045] Example 1: This example provides a high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet, comprising a steel substrate and a zinc-aluminum-magnesium alloy coating formed on the surface of the steel substrate. The zinc-aluminum-magnesium alloy coating contains the following components by mass percentage: aluminum 1.8 wt%, magnesium 1.0 wt%, boron 0.001 wt%, tin 0.03 wt%, with the balance being zinc. The zinc-aluminum-magnesium alloy coating contains a κ-MgZn2 phase, which is in a spherical state and is non-randomly arranged with Fe-BO type interface nails distributed in the interface region between the steel substrate and the coating as nucleation anchors. An Fe-Al inhibition layer is provided between the steel substrate and the coating, and the Fe-Al inhibition layer is embedded in the steel substrate in an undulating serrated shape on the side facing the steel substrate.

[0046] The zinc-aluminum-magnesium alloy coating also includes auxiliary modifying components selected from cerium. The total content of the auxiliary modifying components is 0.01 wt% based on the total mass of the coating of 100 wt%. The spheroidization rate of the κ-MgZn2 phase is 85%, and the equivalent circle diameter distribution of the κ-MgZn2 phase along the cross-sectional direction is 80 nm.

[0047] The continuous hot-dip galvanizing process for the above-mentioned high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet includes the following steps:

[0048] S1. Pre-oxidation treatment: Controlled pre-oxidation treatment is performed on cold-rolled steel sheets after reduction annealing to obtain an oxide substrate.

[0049] The controlled pre-oxidation treatment is as follows: after reduction annealing, the steel plate is introduced into a temporary storage section containing an oxygen atmosphere, the temperature is controlled at 550℃, and the residence time is 3s, so that a nanocrystalline Fe-O transition layer with a thickness of 20-50nm is oxidized and grown on the surface of the steel plate; wherein, the oxygen atmosphere is air and the oxygen volume fraction is 0.5vol.

[0050] S2. Incomplete reduction treatment: The oxide substrate is subjected to incomplete reduction treatment in a hydrogen-containing reducing atmosphere to obtain a pretreated substrate.

[0051] The hydrogen volume fraction in the hydrogen-containing reducing atmosphere is 5 vol%, with the remainder being nitrogen. The reduction treatment temperature is 480℃, and the residence time is 2 seconds. Before the incomplete reduction treatment, the process also includes dust removal treatment on the surface of the oxide substrate to remove loose oxide particles.

[0052] S3. Plating solution preparation and melting: Take aluminum, magnesium, tin and some zinc for mixing. First melt the aluminum and some zinc, then add magnesium and tin raw materials to mix and obtain a basic melt. Then introduce boron into the basic melt in the form of aluminum-boron intermediate alloy and mix evenly. Add the remaining zinc to adjust the bath height to obtain zinc-aluminum-magnesium alloy plating solution.

[0053] The boron mass fraction in the aluminum-boron master alloy is 0.5 wt%. The boron is introduced by adding the aluminum-boron master alloy in small batches with stirring after the base melt temperature reaches 440℃, so that the final boron concentration in the plating solution falls within the range of 0.001 wt%. The auxiliary modifying component cerium is added in the form of a mixed rare earth zinc-cerium master alloy before the remaining zinc is added.

[0054] S4. Hot-dip plating and coating adhesion: After the pretreated substrate is immersed in zinc-aluminum-magnesium alloy plating solution to complete the hot-dip reaction, it is taken out and the adhesion amount of the wet coating on one side of the strip is controlled to be 60g / m², thus obtaining a substrate with wet coating.

[0055] The hot-dip plating solution temperature is 450℃, and the immersion time is 2s. Before immersing the substrate in the zinc-aluminum-magnesium alloy plating solution, the substrate is also pretreated on the surface: the surface of the pretreated substrate is coated with an alcoholic solution of boric acid as a boron source pre-adsorption layer, the boron-containing compound is boric acid, and the coating amount is 0.05mg / m² converted to elemental boron. After coating, it is dried with hot air at 60℃ for 5s.

[0056] S5. Low-temperature temperature control and cooling winding: The substrate with wet coating is placed under airflow to allow the coating to solidify and the κ-MgZn2 phase to spheroidize in situ. Then, it is cooled and wound up to obtain a high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet.

[0057] The process involves holding the surface at 160°C for 30 seconds, followed by air cooling to lower the surface temperature to 80°C before water quenching to complete the winding process.

[0058] Example 2: This example provides a high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet, comprising a steel substrate and a zinc-aluminum-magnesium alloy coating formed on the surface of the steel substrate. The zinc-aluminum-magnesium alloy coating contains the following components by mass percentage: aluminum 2.15 wt%, magnesium 1.5 wt%, boron 0.003 wt%, tin 0.055 wt%, with the balance being zinc. The zinc-aluminum-magnesium alloy coating contains a κ-MgZn2 phase, which is in a spherical state and is non-randomly arranged with Fe-BO type interface nails distributed in the interface region between the steel substrate and the coating as nucleation anchors. An Fe-Al inhibition layer is provided between the steel substrate and the coating, and the Fe-Al inhibition layer is embedded in the steel substrate in an undulating serrated shape on the side facing the steel substrate.

[0059] The zinc-aluminum-magnesium alloy coating also includes auxiliary modifying components selected from titanium. Based on the total mass of the coating (100wt%), the total content of the auxiliary modifying components is 0.2wt%. Titanium exists in the form of aluminum-titanium master alloy inclusions at the κ-MgZn2 phase boundary or η-zinc matrix grain boundary of the coating, and its total titanium content is 0.08wt%. The spheroidization rate of the κ-MgZn2 phase is 90%, and the equivalent circle diameter distribution of the κ-MgZn2 phase along the cross-sectional direction is 165nm.

[0060] The continuous hot-dip galvanizing process for the above-mentioned high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet includes the following steps:

[0061] S1. Pre-oxidation treatment: Controlled pre-oxidation treatment is performed on cold-rolled steel sheets after reduction annealing to obtain an oxide substrate.

[0062] The controlled pre-oxidation treatment is as follows: after reduction annealing, the steel plate is introduced into a temporary storage section containing an oxygen atmosphere, the temperature is controlled at 585℃ and the residence time is 5.5s, so that a nanocrystalline Fe-O transition layer with a thickness of 20-50nm is oxidized and grown on the surface of the steel plate; wherein the oxygen atmosphere is a mixture of air and nitrogen, and the oxygen volume fraction is 2.75 vol.

[0063] S2. Incomplete reduction treatment: The oxide substrate is subjected to incomplete reduction treatment in a hydrogen-containing reducing atmosphere to obtain a pretreated substrate.

[0064] The hydrogen volume fraction in the hydrogen-containing reducing atmosphere is 10 vol%, with the remainder being nitrogen. The reduction treatment temperature is 520℃, and the residence time is 4 s. Before the incomplete reduction treatment, the process also includes purging the surface of the oxide substrate to remove loose oxide particles.

[0065] S3. Plating solution preparation and melting: Take aluminum, magnesium, tin and some zinc for mixing. First melt the aluminum and some zinc, then add magnesium and tin raw materials to mix and obtain a basic melt. Then introduce boron into the basic melt in the form of aluminum-boron intermediate alloy and mix evenly. Add the remaining zinc to adjust the bath height to obtain zinc-aluminum-magnesium alloy plating solution.

[0066] The boron mass fraction in the aluminum-boron master alloy is 2.25 wt%. The boron is introduced by adding the aluminum-boron master alloy in small batches with stirring after the base melt temperature reaches 452.5℃, so that the final boron concentration in the plating solution falls within the range of 0.003 wt%. The auxiliary modifying component titanium is added in the form of aluminum-titanium master alloy during the aluminum melting stage.

[0067] S4. Hot-dip plating and coating adhesion: After the pretreated substrate is immersed in zinc-aluminum-magnesium alloy plating solution to complete the hot-dip reaction, it is taken out and the adhesion amount of the wet coating on one side of the strip is controlled to be 180g / m², thus obtaining a substrate with wet coating.

[0068] The hot-dip plating solution temperature is 455℃, and the immersion time is 4s. Before immersing the substrate in the zinc-aluminum-magnesium alloy plating solution, the pretreated substrate is also subjected to surface pretreatment: the surface of the pretreated substrate is coated with an aqueous solution of borate as a boron source pre-adsorption layer, the boron-containing compound is borate, the coating amount is converted to elemental boron and is 0.275mg / m², and after coating, it is dried with hot air at 90℃ for 12.5s.

[0069] S5. Low-temperature temperature control and cooling winding: The substrate with wet coating is placed under airflow to allow the coating to solidify and the κ-MgZn2 phase to spheroidize in situ. Then, it is cooled and wound up to obtain a high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet.

[0070] The process involves holding the surface at 172.5℃ for 40 seconds, followed by air cooling to lower the surface temperature to 100℃, and then direct air cooling to room temperature to complete the winding process.

[0071] Example 3: This example provides a high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet, comprising a steel substrate and a zinc-aluminum-magnesium alloy coating formed on the surface of the steel substrate. The zinc-aluminum-magnesium alloy coating contains the following components by mass percentage: 2.5 wt% aluminum, 2.0 wt% magnesium, 0.005 wt% boron, 0.08 wt% tin, and the balance being zinc. The zinc-aluminum-magnesium alloy coating contains a κ-MgZn2 phase, which is in a spherical state and is non-randomly arranged with Fe-BO type interface nails distributed in the interface region between the steel substrate and the coating as nucleation anchors. An Fe-Al inhibition layer is provided between the steel substrate and the coating, and the Fe-Al inhibition layer is embedded in the steel substrate in an undulating serrated shape on the side facing the steel substrate.

[0072] The zinc-aluminum-magnesium alloy coating also includes auxiliary modifying components selected from strontium. The total content of the auxiliary modifying components is 0.3 wt% based on the total mass of the coating of 100 wt%. Strontium is introduced in the form of trace strontium-zinc master alloy, and its total strontium content is 0.05 wt%. The spheroidization rate of the κ-MgZn2 phase is 95%, and the equivalent circle diameter distribution of the κ-MgZn2 phase along the cross-sectional direction is 250 nm.

[0073] The continuous hot-dip galvanizing process for the above-mentioned high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet includes the following steps:

[0074] S1. Pre-oxidation treatment: Controlled pre-oxidation treatment is performed on cold-rolled steel sheets after reduction annealing to obtain an oxide substrate.

[0075] The controlled pre-oxidation treatment is as follows: after reduction annealing, the steel plate is introduced into a temporary storage section containing an oxygen atmosphere, the temperature is controlled at 620℃, and the residence time is 8s, so that a nanocrystalline Fe-O transition layer with a thickness of 20-50nm is oxidized and grown on the surface of the steel plate; wherein, the oxygen atmosphere is air, and the oxygen volume fraction is 5.0 vol.

[0076] S2. Incomplete reduction treatment: The oxide substrate is subjected to incomplete reduction treatment in a hydrogen-containing reducing atmosphere to obtain a pretreated substrate.

[0077] The hydrogen volume fraction in the hydrogen-containing reducing atmosphere is 15 vol%, with the remainder being nitrogen. The reduction treatment temperature is 560℃, and the residence time is 6 s. Before the incomplete reduction treatment, the process also includes purging the surface of the oxide substrate to remove loose oxide particles.

[0078] S3. Plating solution preparation and melting: Take aluminum, magnesium, tin and some zinc for mixing. First melt the aluminum and some zinc, then add magnesium and tin raw materials to mix and obtain a basic melt. Then introduce boron into the basic melt in the form of aluminum-boron intermediate alloy and mix evenly. Add the remaining zinc to adjust the bath height to obtain zinc-aluminum-magnesium alloy plating solution.

[0079] The boron mass fraction in the aluminum-boron master alloy is 4 wt%. The boron is introduced by adding the aluminum-boron master alloy in small batches with stirring after the base melt temperature reaches 465℃, so that the final boron concentration in the plating solution falls within the range of 0.005 wt%. The auxiliary modifier strontium is added in the form of strontium-zinc master alloy before the remaining zinc is added.

[0080] S4. Hot-dip plating and coating adhesion: After the pretreated substrate is immersed in zinc-aluminum-magnesium alloy plating solution to complete the hot-dip reaction, it is taken out and the adhesion amount of wet coating on one side of the strip is controlled to be 300g / m², thus obtaining a substrate with wet coating.

[0081] The hot-dip plating solution temperature is 460℃ and the immersion time is 6s. Before immersing the substrate in the zinc-aluminum-magnesium alloy plating solution, the pretreated substrate is also subjected to surface pretreatment: an alcohol solution of an organoboroate is coated on the surface of the pretreated substrate as a boron source pre-adsorption layer. The boron-containing compound is an organoboroate, and the coating amount is 0.5mg / m² converted to elemental boron. After coating, it is dried with hot air at 120℃ for 20s.

[0082] S5. Low-temperature temperature control and cooling winding: The substrate with wet coating is placed under airflow to allow the coating to solidify and the κ-MgZn2 phase to spheroidize in situ. Then, it is cooled and wound up to obtain a high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet.

[0083] The process involves holding the surface at 185°C for 50 seconds, followed by air cooling to lower the surface temperature to 120°C, and then direct air cooling to room temperature to complete the winding process.

[0084] Comparative Example 1: This comparative example is the same as that in Example 1, except that the zinc-aluminum-magnesium alloy coating does not contain boron. The rest of the contents are the same as those in Example 1.

[0085] Comparative Example 2: This comparative example is the same as that in Example 1, except that the zinc-aluminum-magnesium alloy coating does not contain tin. The rest of the contents are the same as those in Example 1.

[0086] Comparative Example 3: This comparative example refers to the content of Example 1, except that the S1 pre-oxidation treatment was not performed, and the S2 incomplete reduction treatment was performed directly after reduction annealing. The rest of the content is the same as Example 1.

[0087] Comparative Example 4: This comparative example refers to the content of Example 1, except that the S2 incomplete reduction treatment was not performed, and the S3 plating solution preparation and melting steps were carried out directly after the pre-oxidation treatment. The rest of the content is the same as Example 1.

[0088] Comparative Example 5: This comparative example refers to the content of Example 1, except that in the S4 hot-dip plating and coating adhesion step, the pretreated substrate was not pretreated before being immersed in the zinc-aluminum-magnesium alloy plating solution, that is, no boric acid alcohol solution was coated as a boron source pre-adsorption layer. The rest of the content is the same as Example 1.

[0089] Comparative Example 6: This comparative example is the same as that in Example 1, except that the zinc-aluminum-magnesium alloy coating does not contain cerium-assisted modification components. The rest of the contents are the same as those in Example 1.

[0090] Sample preparation: Samples with dimensions of 150mm × 150mm were cut from the hot-dip galvanized aluminum-magnesium sheets prepared in Examples 1, 2, 3 and Comparative Examples 1 to 6 along the rolling direction. All samples were ultrasonically cleaned with acetone to remove surface oil, then rinsed with anhydrous ethanol and dried with cold air. Three parallel samples were prepared for each set of parameters to eliminate random errors.

[0091] Planar corrosion resistance test: The prepared sample was placed in a neutral salt spray test chamber and sprayed continuously with 5wt% NaCl solution at a constant temperature of 35℃ according to relevant standards. The spray deposition rate was controlled at 1-2 mL / (80cm²·h), and the test cycle was 720h. During the test, the time and area percentage of red rust appearing on the sample surface were observed and recorded at regular intervals to evaluate the corrosion resistance of the coating in the planar area. The standard for this test was GB / T10125-2012 "Artificial Atmosphere Corrosion Test - Salt Spray Test".

[0092] Corrosion resistance test of the cut surface: Using a carbide tool, a diagonal cut was made on the sample surface to expose the steel substrate, ensuring that the cut penetrated the entire coating. The sample was then immersed in a 3.5 wt% NaCl solution. An electrochemical workstation was used to measure the electrochemical impedance spectroscopy of the cut area, with a scanning frequency range of 0.01 Hz to 100 kHz. The migration resistance and hindrance effect of chloride ions at the cut were evaluated by analyzing the change in impedance modulus in the low-frequency region. This test was performed according to GB / T24196-2009 "Electrochemical Test Methods for Corrosion of Metals and Alloys – Measurement of Potentiostatic and Potentiodynamic Polarizations".

[0093] Bending adhesion stability test: The sample was subjected to repeated 180° bending tests at room temperature, with a bending radius equal to one time the plate thickness. The bending rate was kept constant until visible peeling or cracks appeared on the outer surface of the sample. The number of bends at this point was recorded. Subsequently, a metallographic section was prepared at the bending fracture point, and the microstructure of the interface between the coating and the steel substrate was observed using a scanning electron microscope to evaluate the degree of serrated embedding of the Fe-Al inhibition layer and the interfacial bonding strength. The standard for this test was GB / T232-2010 "Metallic Materials - Bending Test Method".

[0094] Microstructure and interface structure characterization: Field emission scanning electron microscopy and its accompanying energy dispersive spectroscopy (EDS) were used to observe the cross-section of the coating, focusing on the distribution morphology, equivalent circle diameter, and sphericity of the κ-MgZn2 phase. Simultaneously, the presence of Fe-BO type interfacial studs at the steel substrate-coating interface and their spatial correspondence with the κ phase were analyzed. X-ray diffraction was used to determine the composition and structure of each phase in the coating. The experimental standards were GB / T13298-2015 "Methods for Examination of Microstructure of Metals" and GB / T8362-2018 "Methods for Analysis of Residual Elements in Steel".

[0095] Table 1: Results of Planar Corrosion Resistance Test

[0096] Example 1 412 3.2 Example 2 537 1.9 Example 3 589 1.1 Comparative Example 1 168 27.6 Comparative Example 2 325 7.9 Comparative Example 3 246 15.3 Comparative Example 4 219 19.7 Comparative Example 5 283 11.4 Comparative Example 6 376 4.7

[0097] Table 2: Results of Corrosion Resistance Test of Cut Section

[0098] Example 1 12870 Example 2 17540 Example 3 21360 Comparative Example 1 3210 Comparative Example 2 8920 Comparative Example 3 5640 Comparative Example 4 4780 Comparative Example 5 7350 Comparative Example 6 10690

[0099] Table 3: Results of Bending Adhesion Stability Test

[0100] Example 1 27 Example 2 36 Example 3 42 Comparative Example 1 9 Comparative Example 2 21 Comparative Example 3 13 Comparative Example 4 11 Comparative Example 5 18 Comparative Example 6 24

[0101] Table 4: Characterization results of microstructure and interface structure

[0102] Example 1 85 80 12.7 Example 2 90 165 17.9 Example 3 95 250 24.1 Comparative Example 1 42 320 0.8 Comparative Example 2 76 94 11.2 Comparative Example 3 63 142 5.6 Comparative Example 4 58 176 4.3 Comparative Example 5 71 108 7.9 Comparative Example 6 82 87 11.9

[0103] Example Conclusion:

[0104] As can be seen from Examples 1-3 and Comparative Example 1, and Tables 1, 2 and 3, adding trace amounts of boron to the coating can improve the overall performance of the coating. The working principle is that boron promotes the formation of a strong and tough interface structure in the interfacial reaction, thereby enhancing the bonding force between the coating and the steel substrate, making the product less prone to peeling when subjected to deformation. At the same time, this optimization of the microstructure also slows down the erosion rate of the corrosive medium on the substrate, resulting in excellent overall corrosion resistance and cut protection capabilities.

[0105] Based on Examples 1-3 and Comparative Example 2, and in conjunction with Tables 1, 2 and 3, it can be seen that the introduction of trace amounts of tin in the coating plays a synergistic protective role in the system, especially forming an effective barrier at the cut surface, which enhances the resistance to chloride ion migration. This results in the plate exhibiting good corrosion resistance at the cut edge, and also helps to improve the overall corrosion resistance life and bending crack resistance of the coating.

[0106] As can be seen from Examples 1-3 and Comparative Example 3, and from Tables 1, 2 and 3, the pre-oxidation treatment step is an important condition for achieving high-performance coatings. This process constructs a suitable transition layer on the steel substrate surface, inducing the formation of a serrated inhibition layer and specific interface anchors. This structure endows the coating with good mechanical interlocking force and adhesion stability, making it less prone to failure during processing. It also enhances the corrosion resistance of the plane and avoids early corrosion caused by poor interface bonding.

[0107] Based on Examples 1-3 and Comparative Example 4, and in conjunction with Tables 1, 2, and 3, it can be seen that the incomplete reduction treatment step plays a role in ensuring the quality of the coating. This step optimizes the chemical activity state of the substrate surface, ensuring the uniformity and density of the subsequent interface reaction. At the same time, the improved coating adhesion strength and enhanced corrosion protection effectively prevent the risk of coating peeling under bending or impact, and extend the service life of the material in the environment.

[0108] As can be seen from Examples 1-3 and Comparative Example 5, and Tables 1, 2 and 3, the surface pretreatment before hot-dip plating has a significant effect. By introducing boron-containing compounds into the substrate surface in advance, the driving force of chemical reaction at the interface is strengthened, making the coating bond with the substrate more tightly and firmly. This not only improves the product's resistance to bending and peeling, but also enhances the overall corrosion resistance, demonstrating the impact of surface pretreatment on the final product quality.

[0109] As can be seen from Examples 1-3 and Comparative Example 6, and Tables 1, 2 and 3, the addition of auxiliary modifying components has a synergistic effect. These components can further optimize the microstructure of the coating, purify the interface area and refine the grains. This improves the density and uniformity of the coating, resulting in better corrosion resistance and higher interfacial bonding strength than the basic formulation, thus improving product quality.

[0110] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A high corrosion resistant zinc-aluminum-magnesium alloy plated sheet material, characterized by, The coating comprises a steel substrate and a zinc-aluminum-magnesium alloy coating formed on the surface of the steel substrate. The zinc-aluminum-magnesium alloy coating contains the following components by mass percentage: Al: 1.8–2.5 wt%, Mg: 1.0–2.0 wt%, B: 0.001–0.005 wt%, Sn: 0.03–0.08 wt%, with the balance being Zn. The zinc-aluminum-magnesium alloy coating contains a κ-MgZn2 phase, which is in a spherical state and is non-randomly arranged with Fe-BO type interface nails distributed in the interface region between the steel substrate and the coating as nucleation anchors. An Fe-Al inhibition layer is provided between the steel substrate and the coating, and the Fe-Al inhibition layer is embedded in the steel substrate in an undulating serrated shape on the side facing the steel substrate.

2. The high corrosion resistant zinc-aluminum-magnesium alloy plated sheet according to claim 1, characterized by, The zinc-aluminum-magnesium alloy coating further includes one or more auxiliary modifying components selected from Re, Ti, or Sr, and the total content of the auxiliary modifying components is 0.01 to 0.3 wt% based on the total mass of the coating being 100 wt%.

3. The high corrosion resistant zinc-aluminum-magnesium alloy coated sheet product of claim 2, wherein, When the auxiliary modifying component contains Re, the Re element is Ce or La; when the auxiliary modifying component contains Ti, Ti exists in the form of Al-Ti master alloy inclusions or TiB2 / TiC ceramic particles at the κ-MgZn2 phase boundary or η-Zn matrix grain boundary of the coating, and its total Ti content is 0.01-0.15 wt%; when the auxiliary modifying component contains Sr, Sr is introduced in the form of trace Sr-Zn master alloy, and its total Sr content is 0.005-0.05 wt%.

4. The high corrosion resistant zinc-aluminum-magnesium alloy plated sheet according to claim 1, characterized by, The sphericity of the κ-MgZn2 phase is ≥85%, and the equivalent circle diameter distribution of the κ-MgZn2 phase along the cross-sectional direction is 80-250 nm.

5. A continuous hot-dip galvanizing process for a high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet, characterized in that, The high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet according to any one of claims 1-4 includes the following steps: S1. Pre-oxidation treatment: Controlled pre-oxidation treatment is performed on cold-rolled steel sheets after reduction annealing to obtain an oxide substrate. S2. Incomplete reduction treatment: The oxide substrate is subjected to incomplete reduction treatment in a hydrogen-containing reducing atmosphere to obtain a pretreated substrate. S3. Plating solution preparation and melting: Take Al, Mg, Sn and a portion of Zn for batching. Melt Al and a portion of Zn first, then add Mg and Sn raw materials to mix and obtain a basic melt. Then introduce B into the basic melt in the form of Al-B intermediate alloy or boron powder and mix evenly. Add the remaining Zn to adjust the bath height to obtain a zinc-aluminum-magnesium alloy plating solution. S4. Hot-dip plating and coating adhesion: The pretreated substrate is immersed in the zinc-aluminum-magnesium alloy plating solution to complete the hot-dip reaction and then taken out. The amount of wet coating on one side of the strip is controlled to be 60-300g / m², and a substrate with wet coating is obtained. S5. Low-temperature temperature control and cooling winding: The substrate with the wet coating is placed under airflow to allow the coating to solidify and the κ-MgZn2 phase to spheroidize in situ. Then, it is cooled and wound up to obtain a high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet.

6. The continuous hot-dip galvanizing process for a high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet according to claim 5, characterized in that, In step S1, the controlled pre-oxidation treatment is as follows: after the reduction annealing, the steel plate is introduced into a temporary storage section containing an oxygen atmosphere, and the temperature is controlled at 550-620°C and the residence time is 3-8s, so that a nanocrystalline Fe-O transition layer with a thickness of 20-50nm is oxidized and grown on the surface of the steel plate; wherein the oxygen atmosphere is air or a mixture of air and nitrogen, and the oxygen volume fraction is 0.5-5.0%.

7. The continuous hot-dip galvanizing process for a high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet according to claim 5, characterized in that, In step S2, the volume fraction of H2 in the hydrogen-containing reducing atmosphere is 5-15 vol%, with the balance being N2. The reduction treatment temperature is 480-560℃, and the residence time is 2-6 s. Before the incomplete reduction treatment, the process further includes dust removal or purging of the oxide substrate surface to remove loose oxide particles.

8. The continuous hot-dip galvanizing process for a high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet according to claim 5, characterized in that, In step S3, the mass fraction of B in the Al-B master alloy is 0.5–4 wt%. The introduction is as follows: after the basic melt temperature reaches 440–465 °C, the Al-B master alloy is added in small batches with stirring, so that the final concentration of B in the plating solution falls within the range of 0.001–0.005 wt%. Alternatively, one or more auxiliary modifying components selected from Re, Ti, or Sr can be selectively added. When Ti is added, it is added in the form of Al-Ti master alloy during the Al melting stage. When Re is added, it is added in the form of mixed rare earth Zn-Re master alloy before the remaining Zn is added.

9. The continuous hot-dip galvanizing process for a high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet according to claim 5, characterized in that, In step S4, the temperature of the hot-dip plating solution is 450–460°C, and the immersion time is 2–6 seconds. Before immersing the pretreated substrate in the zinc-aluminum-magnesium alloy plating solution, the pretreated substrate is also subjected to surface pretreatment: the surface of the pretreated substrate is coated with an alcoholic solution or aqueous solution containing boron compounds as a boron source pre-adsorption layer. The boron-containing compounds are boric acid, borate, or organic borate esters. The coating amount is 0.05–0.5 mg / m² converted to elemental boron. After coating, the substrate is dried with hot air at 60–120°C for 5–20 seconds.

10. The continuous hot-dip galvanizing process for a high corrosion-resistant zinc-aluminum-magnesium alloy coated sheet according to claim 5, characterized in that, In step S5, the resting is to maintain the surface temperature at 160-185°C for 30-50 seconds; then, the surface temperature is cooled by airflow to 80-120°C before water quenching or direct air cooling to room temperature to complete the winding.